2019
DOI: 10.1080/0966369x.2018.1555148
|View full text |Cite
|
Sign up to set email alerts
|

A feminist geographic analysis of perceptions of food and health in Ugandan cities

Abstract: This article contributes to a feminist geographic analysis of how urban food and health environments and noncommunicable disease experience may be being constructed, and contested, by healthcare professionals (local elites) in two secondary Ugandan cities (Mbale and Mbarara). I use thematic and group interaction analysis of focus group data to explore material and discursive representations. Findings make explicit how healthcare professionals had a tendency to prescribe highly classed and gendered assumptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…These ideas were common in my male interviewees, but a good number of women themselves made such statements. My earlier research with local healthcare professionals revealed similar discussions (Mackay 2019a). In my interviews, I probed such claims by asking about women who stayed at home (so-called urban housewives 9 ).…”
Section: Livelihood Strategies and Tactics Perceived As Contributors To Non-communicable Diseasesmentioning
confidence: 81%
See 4 more Smart Citations
“…These ideas were common in my male interviewees, but a good number of women themselves made such statements. My earlier research with local healthcare professionals revealed similar discussions (Mackay 2019a). In my interviews, I probed such claims by asking about women who stayed at home (so-called urban housewives 9 ).…”
Section: Livelihood Strategies and Tactics Perceived As Contributors To Non-communicable Diseasesmentioning
confidence: 81%
“…Awareness of how unequal and unjust socioeconomic and health systems, together with features of the urban built environment, work as factors contributing to NCD experience, was apparent in many of my individual interviews, and in earlier discussions with local healthcare professionals (Mackay 2019a). Policy or practical intervention strategies to combat growing NCD burden must investigate not only the medical/biological causes, but also the socio-cultural and environmental influences (SDHs).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations